Subjective Well-Being Among Unaccompanied Refugee Youth: Longitudinal Associations With Discrimination and Ethnic Identity Crisis - Oppedal, Brit; Keles, Serap; Røysamb, Espen (Frontiers in Psychology, 2022)
Unaccompanied refugee youth (URY), who as children fled their countries to seek asylum in a foreign country without the company of an adult legal caretaker are described as being in a vulnerable situation. Many of them struggle with mental reactions to traumatic events experienced pre-migration, and to the daily hassles they face after being granted asylum and residence. Despite continuous high levels of mental health problems URY demonstrate remarkable agency and social mobility in the years after being granted asylum in their destination countries. A sense of subjective wellbeing (SWB) may enable resilient outcomes in people exposed to past or ongoing adversities. To fill the gap in the research literature about positive psychological outcomes among URY, the overall aim of this study was to explore the longitudinal associations between SWB and two taxing acculturation hassles: perceived discrimination and ethnic identity crisis. Three annual waves of self-report questionnaire data were collected from a population-based sample of URY; n = 581, Mage = 20.01(SD=2.40), Mlength of stay = 4.63 (SD= 4.40), 82 % male, mainly from Afghanistan, Somalia, Iraq, and Sri Lanka. The longitudinal associations between SWB, perceived discrimination and ethnic identity crisis across time were analysed using auto-regressive cross-lagged modelling. The results revealed that perceived discrimination, but not ethnic identity crisis, negatively predicted subsequent levels of SWB. More importantly, high levels of SWB at one timepoint predicted decreases in both discrimination and ethnic identity crisis at subsequent timepoints. Further, increases in SWB from one timepoint to the next was associated with significant co-occurring decreases in both discrimination and ethnic identity crisis, and vice versa. Despite the negative effect of perceived discrimination on SWB, promoting SWB in URY can protect them from future hazards of acculturation hassles in complex ways. We underscore the need for more research on SWB among URY and other refugee youth. We further discuss the potential of SWB to foster resilient outcomes in young refugees and suggest that interventions to strengthen SWB among them should consider their transnational and multicultural realities and experiences.